Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.29058/mjwbs.906629
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Basic Depression Scale For Turkey

Abstract: Aim: To investigate the validity and reliability of the Basic Depression Scale for Turkey. It was designed and carried out in the form of cross-sectional research methodologically. Material and Methods: Data analysis for structure validity; Cronbach alpha (α) coefficient used in reliability analysis. Factor analysis applied for validity analysis. Results: Basic Depression Scale found to have sufficient distribution based on the explanatory factor analysis of the Kaiser Meyer Olkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Usually, the test-retest correlation coefficient criterion was set at 0.6 28,35 . The test-retest reliability was considered satisfactory when the test-retest correlation coefficient was larger than 0.6 48–50 . Data analysis results showed the test-retest reliability from all the reviewed studies using it was greater than 0.6, ranging from 0.79 to 0.99.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the test-retest correlation coefficient criterion was set at 0.6 28,35 . The test-retest reliability was considered satisfactory when the test-retest correlation coefficient was larger than 0.6 48–50 . Data analysis results showed the test-retest reliability from all the reviewed studies using it was greater than 0.6, ranging from 0.79 to 0.99.…”
Section: Resultsmentioning
confidence: 99%
“…12 31 AA patients, 29 vitiligo patients, and 30 control patients volunteered to participate in the study of Erdogan et al There was no statistically significant difference between the patients with AA and the control group according to the BDI (p = 0.110) inventory. 21 In studies investigating the prevalence of anxiety in adult AA patients, point prevalence rates were reported as 3.24%, 4 4%, 3 8.4%, 20 and 13.70%. 12 In addition, some case-control studies reported that people with AA had a higher chance of being diagnosed with an anxiety disorder compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…10 Turkish validity and reliability of all these scales have been demonstrated. [12][13][14] All participants were evaluated by the same physiatrist for the diagnosis of FMS with the 2016 American College of Rheumatology criteria.…”
Section: Methodsmentioning
confidence: 99%